Prohibition of torture and inhuman or degrading treatment in the Polish legal system from a criminal law perspective - Luniewska, Klaudia (Central European Academy Law Review, 2023)
The purpose of this chapter is to analyse the Polish legal system in relation to the prohibition of torture and inhuman treatment from constitutional and criminal law perspectives. These issues will be presented based on the analysis of current regulations, as well as through the interpretation of the hitherto developed doctrine, in addition to the opinions of Polish authorities in the field of the protection of human and civil rights and freedoms. As part of these considerations, conclusions are also presented from an analysis of Polish jurisprudence regarding the prohibition of torture in correlation with the use of violence by public officials to extort confessions, the abuse of a person deprived of liberty, and the abuse of power, which are subject to a separate classification under Polish criminal law.